American war stories - Boyle, Brenda M., 1957- (New Brunswick : Rutgers University Press, 2021)
"American War Stories asks readers to contemplate what traditionally constitutes a "war story" and how that constitution obscures the normalization of militarism in American culture. The book claims the traditionally narrow scope of "war story," as by a combatant about his wartime experience, compartmentalizes war, casting armed violence as distinct from everyday American life. Broadening "war story" beyond the specific genres of war narratives such as "war films," "war fiction," or "war memoirs," American War Stories exposes how ingrained militarism is in everyday American life, a condition that challenges the very democratic principles the United States is touted as exemplifying"--
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 29, 2020).
eBooks on EBSCOhost
Keywords: War and society -- United States; Militarism -- United States; War stories, American; United States -- History, Military -- 21st century; Guerre et société -- États-Unis.; Militarisme -- États-Unis.; Récits de guerre américains.; États-Unis -- Histoire militaire -- 21e siècle.; Military; BIOGRAPHY & AUTOBIOGRAPHY; United States; Historical Events; Subjects & Themes; LITERARY CRITICISM; History & Criticism; Film & Video; PERFORMING ARTS; Violence in Society; SOCIAL SCIENCE; Media Studies; Militarism; War and society; War stories, American; United States; 2000-2099; Electronic books; Military history